Sex-specific threat responding and neuronal engagement in carbon dioxide associated fear and extinction: Noradrenergic involvement in female mice - Rebecca Ahlbrand; Allison Wilson; Patrick Woller; Yuv Sachdeva; Jayden Lai; Nikki Davis; James Wiggins; Renu Sah (Neurobiology of Stress, 2024)
Difficulty in appropriately responding to threats is a key feature of psychiatric disorders, especially fear-related conditions such as panic disorder (PD) and posttraumatic stress disorder (PTSD). Most prior work on threat and fear regulation involves exposure to external threatful cues. However, fear can also be triggered by aversive, within-the-body, sensations. This interoceptive signaling of fear is highly relevant to PD and PTSD but is not well understood, especially in the context of sex. Using female and male mice, the current study investigated fear-associated spontaneous and conditioned behaviors to carbon dioxide (CO2) inhalation, a potent interoceptive threat that induces fear and panic. We also investigated whether behavioral sensitivity to CO2 is associated with delayed PTSD-relevant behaviors. CO2 evoked heterogenous freezing behaviors in both male and female animals. However, active, rearing behavior was significantly reduced in CO2-exposed male but not female mice. Interestingly, behavioral sensitivity to CO2 was associated with compromised fear extinction, independent of sex. However, in comparison to CO2-exposed males, females elicited less freezing and higher rearing during extinction suggesting an engagement of active versus passive defensive coping. Persistent neuronal activation marker ΔFosB immuno-mapping revealed attenuated engagement of infralimbic-prefrontal areas in both sexes but higher activation of brain stem locus coeruleus (LC) area in females. Inter-regional co-activation mapping revealed sex-independent disruptions in the infralimbic-amygdala associations but altered LC associations only in CO2-exposed female mice. Lastly, dopamine β hydroxylase positive (DβH + ve) noradrenergic neuronal cell counts in the LC correlated with freezing and rearing behaviors during CO2 inhalation and extinction only in female but not male mice. Collectively, these data provide evidence for higher active defensive responding to interoceptive threat CO2-associated fear in females that may stem from increased recruitment of the brainstem noradrenergic system. Our findings reveal distinct contributory mechanisms that may promote sex differences in fear and panic associated pathologies.